2016
DOI: 10.1103/physrevb.94.165447
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond-laser induced dynamics of CO on Ru(0001): Deep insights from a hot-electron friction model including surface motion

Abstract: A Langevin model accounting for all six molecular degrees of freedom is applied to femtosecond-laser induced, hot-electron driven dynamics of Ru(0001)(2 × 2):CO. In our molecular dynamics with electronic friction approach, a recently developed potential energy surface based on gradient-corrected density functional theory accounting for van der Waals interactions is adopted. Electronic friction due to the coupling of molecular degrees of freedom to electron-hole pairs in the metal are included via a local densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Details on the PES are reported in Refs. [31,32], but we mention that DFT calculations were carried out using the RPBE functional [34] with D2 [35] van der Waals correction, which yields E ads = 1.69 eV, close to the experimental value. In our calculations, we also allow for the possibility of energy transfer from the molecule to the surface via (i) excitation of surface atom motion and (ii) electron-hole pair excitations at the surface region.…”
supporting
confidence: 65%
“…Details on the PES are reported in Refs. [31,32], but we mention that DFT calculations were carried out using the RPBE functional [34] with D2 [35] van der Waals correction, which yields E ads = 1.69 eV, close to the experimental value. In our calculations, we also allow for the possibility of energy transfer from the molecule to the surface via (i) excitation of surface atom motion and (ii) electron-hole pair excitations at the surface region.…”
supporting
confidence: 65%
“…The Ru parameters entering the 2TM are those of Refs. [9,11,38] and are summarized in the caption of Fig. 1.…”
Section: Methods: Aimdef Applied To Dimetmentioning
confidence: 99%
“…Electronic temperature calculated from the 2TM using the implementation and the same material parameters of Refs [9,11,38]. for Ru(0001) and a Gaussian laser pulse of 800 nm wavelength, 130 fs FWHM, and fluence F = 60 J/m 2 .…”
mentioning
confidence: 99%
“…Still, there are processes also occurring at this time scale for which the use of thermostats can be relevant as, for example, reactions induced by femtosecond laser pulses. In this respect, it has recently been shown that the desorption of O 2 from Ag(110) [52,53] and, in particular, the desorption of CO from Ru(0001) [54] is induced to a great extent by the hot surface lattice created by the laser. Thus, we anticipate that the use of thermostats together with the AIMDEF scheme, which is also adapted for describing time-dependent electronic temperatures [55], can be a powerful tool to simulate and understand surface femtochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The random force R[T e ,η i (r i )] (third term) describes the effect of e-h pair excitations and deexcitations for nonzero electronic temperatures T e and it is commonly approximated by a Gaussian white noise of variance Var[R(T e ,η i )] = (2k B T e η i )/ t, where k B is the Boltzmann constant and t is the integration time step. The R(T e ,η i ) term is crucial when describing desorption processes induced by femtosecond laser pulses [47][48][49][50][51][52][53][54][55], but it can safely be neglected in simulations of common molecular beam experiments, which are usually performed at surface temperatures of a few hundred Kelvin for which the e-h pair distribution hardly deviates from its ground state at 0 K. Regarding the surface atoms, the constant surface temperature conditions are simulated by thermalizing all or part of the mobile surface atoms (see below) with the Nosé-Hoover thermostat [43,44]. In the Nosé-Hoover thermostat, the real system is coupled to a dimensionless dynamical variable s that together with its conjugate momentum p s act as a thermal bath, i.e., ensure a canonical distribution in the real system.…”
Section: Theoretical Methodsmentioning
confidence: 99%